Mediating Effect of Online Shopping Satisfaction Between Online Shopping Experience and Customer Loyalty - Bagus Rizaldi Ravsyanjani; Endang Pamularsih; Fazry Wildan; Artha Sejati Ananda (Green Publisher Indonesia, 2025)
This study wants to know what factors influence customer satisfaction which can lead to loyalty in the online shopping context by looking at the phenomena and problems faced by customers. The previous research was used as literature for this study with a quantitative method to see the impact of independent variables on the dependent variable and descriptive analysis for regression results. The authors pointed out factors of e-fulfillment: condition, timeliness, availability, ease of return, e-business quality, and product quality have effects on the satisfaction and loyalty of customers in online shopping. The sample for this study still does not adequately describe the population because it only uses snowball sampling. This study can help online shop owners, entrepreneurs, researchers, and students to get literature on e-fulfillment factors that can affect customer satisfaction and make repeat transactions. This study modifies the e-fulfillment factors that influence customer satisfaction and loyalty in the context of online shopping in Indonesia.